Keterlaksanaan asas kerahasiaan dalam konseling pada peserta didik dengan kondisi broken home - Kadek Sinta Ayu Pramesti; Kadek Suranata; I Ketut Dharsana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study is the result of a literature review that discusses the implementation of the confidentiality principle in counseling students with broken home conditions. The results of the study show that counseling services with the principle of confidentiality for students with broken home conditions have a role in improving and achieving the lives of students both related to problem alleviation and optimal development in learning. The existence of children in this broken home situation can lead to negative behaviors that impact bad habits at home, socializing with peers, academics. and conduct disorder in school. Negative behaviors by children can lead to juvenile delinquency. Juvenile delinquency arises due to the absence of family and/or environmental recognition so that they feel that their basic needs, namely love and affection, are neglected. Not fulfilling the need for love is the basis for young people or adolescents to commit deviant actions. The principle of confidentiality is used when students have problems and the teacher/counselor must be able to keep it secret. However, this secrecy has limitations that must be considered between the interests of the school or educational institution and the interests of the students themselves. Students who wish to consult with the teacher/counselor can be influenced by the way the teacher himself provides services and maintains the confidentiality of the student's problems. The better the method used in maintaining the confidentiality of the students, the more successful the teacher will be in guiding.